An Analysis on The Quality of Reading Materials Using Textbook at The Ninth Grade Of Junior High School - A. Mudrikatul Adawiyah; Hasnawati Latief; Sitti Maryam Hamid (FKIP Unismuh Makassar, 2026)
Textbooks play a pivotal role in supporting English language learning; therefore, evaluating their quality is essential to ensure alignment with current curriculum standards. This study examines the ninth-grade English textbook Think Globally, Act Locally, published by the Ministry of Education and Culture of the Republic of Indonesia, to assess its content and language quality based on the National Education Standards Agency (BSNP) criteria. Employing a qualitative descriptive design with document analysis, the study identifies the textbook's strengths, including its contextualized learning materials, extensive reading activities, and engaging visual presentation. The findings reveal that the textbook achieves a content suitability score of 78.12% and a language feasibility score of 75%, indicating that it generally meets BSNP standards. This study contributes empirical evidence on the quality of government-issued English textbooks and provides valuable insights for teachers, curriculum developers, and policymakers in selecting and improving instructional materials.